Analisa Produktivitas Tenaga Kerja Pada Pekerjaaan Rangka Atap - Mulyadi Mulyadi; Hasnawati Hasnawati; Muhammad Ridha (Jurnal Teknik Sipil Unaya, 2019)
Productivity is an important factor in determining the success of a construction work. Increased productivity will reduce work time, and that means it will reduce costs. In general, the value of productivity is determined by the factor of the volume of work, implementation time, and the number of workers. In order to get the job done well, a planning effort is needed by paying attention to these factors. For this reason, this study was conducted to determine the value of productivity in one component of building construction work, namely lightweight steel roof truss work. The object of study was the work of lightweight steel roof truss 4 (four) project sites, namely the 4 x 25 Shop Houses Construction Project in Meulaboh, West Aceh, the Building of the Rector & Administration Bureau Building of STKIP Bina Bangsa Getsempena Banda Aceh, the Construction of the Getsempena Lhoksukon North Aceh STIKES Building and the Construction of North Aceh RIKI STIKes Building, Bina Nusantara Idi, East Aceh. The roof truss material used is type C Truss 75 0.75 Thickness. The volume of roof truss work is planned to be 2022.38 m2. The study was conducted through field observations by directly recording the volume of work, the duration of each stage of work, and the number of workers involved. The results of the analysis show that the productivity value for roof truss works is obtained by an average of 2,062 m2 / hour or 16,499 m2 / day. In the implementation of roof truss work, the amount of labor used is the same in all segments, so the value of productivity tends to be determined by the magnitude of the ratio between the volume of work and the effective time of implementation. Thus, if the amount of work volume can be completed in a shorter time then the value of productivity will increase